Relationship Between Ethical Leadership Through Leader Practices Of Decision Making, Two-way Communication, Reinforcement And Ethical Climate - Umi Hamidaton Mohd Soffian Lee; Razaleigh Muhamat @ Kawangit; Zaleha Yazid (Human Resource Management Academic Research Society, 2024)
Volume 9 No: 5